An Extensive Survey of the Historic Center of Cusco for Its Seismic Vulnerability Assessment - Spacone, E.; Brando, G.; Peruch, M.; Mazzanti, C.; Sovero, K.; Tarque, N. (Springer Netherlands, 2019)
This paper presents the main important typological data collected during an extensive survey carried out on the buildings of the historic center of Cusco, Peru. These data will represent the basis for a future analysis devoted to large scale seismic vulnerability assessment, to develop, in a structured and efficient manner, policies and measures for the seismic risk mitigation. Starting from the collection of available data and from the historical analysis of the urban development of the center, also accounting for earthquakes of the past, the most representative architectural typologies are identified. Moreover, statistical analyses are carried out, in order to detect the most recurrent structural details. On these bases, the main potential fragilities are identified, giving a preliminary idea of the structural behavior of the considered buildings under seismic forces.
Keywords: Vulnerability (computing); Vulnerability assessment; Scale (ratio); Center (category theory); Geography; Civil engineering; Seismology; Geology; Forensic engineering; Cartography; Computer science; Engineering; Computer security; https://purl.org/pe-repo/ocde/ford#2.01.04